Growth and Production of Water Spinach (Ipomea aquatica Forsk) in Various Types of Hydroponic Nutrition System NFT (Nutrient Film Technique) - Payumi; Oktavianus Lumban Tobing; Nani Yulianti; Nur Rochman (Universitas Djuanda, 2022)
Efforts to increase the production of kale with a hydroponic cultivation system, the addition of nutrients is absolutely necessary for both macro and micronutrients. In addition to using AB mix nutrients, the use of other alternative fertilizers in hydroponic cultivation needs to be a big concern so that it can suppress the use of inorganic fertilizers. The purpose of this study was to determine the effect of giving various types of nutrient compositions AB mix and cow urine on the growth and yield of water spinach plants with the Nutrient Film Technique (NFT) hydroponic system . The design used in this study was a single factor randomized block design (RAK) with 4 levels of treatment of various types of hydroponic nutrients consisting of N 1 (100% AB mix ), N 2 (75% AB mix + 25% Cow Urine), N 3 (50% AB mix + 50% Cow Urine), and N 4 (25% AB mix + 75% Cow Urine). The results of this study showed that the provision of various nutritional compositions significantly affected the growth and productivity of kale except for the variable number of books. Plant water spinach given nutritional composition N 4 (25% AB mix + 75% of cow urine) showed a markedly lower in all the observed variables, while the growth and productivity of water spinach best shown in the nutritional composition of 100% AB mix but not significantly different the nutritional composition treatment was 75% AB mix + 25% cow urine and 50% AB mix + 50% cow urine. The results of this study also show that the use of cow urine has not been able to replace the use of AB mix nutrition.